The Effect of Sample Size on the Strength of High-Strength Concrete Containing Silica Fume - Assi, Dunyazad K. (Sulaimani Journal for Engineering Sciences, 2023)
Concrete samples during concreting works according to different standards in different countries. On the other hand, it is known that different shapes and sizes of concrete samples can cause variations in results of compressive strength or splitting tensile strength, consequently on the relationship between the two mentioned stresses. This study concentrated on the effect of specimen sizes on concrete's compressive and splitting tensile strength. For this purpose, three different mixes are designed for four different grades of high-strength concretes 60, 70, 80, and 90. Each mixture has different percentages of silica fume 8%, 10.5 and 12%. Moreover, 2% is added for all of the four mixes. Hence, 48 cylinders of different sizes were cast. The specimens are tested for both compressive and splitting strength at 28 days. At the end of the experimental study, compressive strength and splitting tensile strength were performed, and some analyses were performed to obtain conversion factors and relations among these factors and results. The results of analyses indicate that for all testing conditions, there is a strong influence of variation in the size of the specimens, which is evident from the test results. Hence, the small size of the cylinders, which is 70 mm, recorded a higher compressive strength of 8% more than the cylinders of 150 mm diameters. This was concluded also for the case of splitting tensile strengths. However, this difference was different with increasing the grade of concrete, i.e., with an increase in the percentage of SF. The distinction of the ratio of split strength of 100m diameter to the tensile of 150 mm dia. and between the split strength of 70 mm dia. to the strength of 150 mm dia. was only 4%.
Keywords: Compressive strength; High strength concrete; Size effect; splitting tensile strength